Rancang Bangun Alat Pencuci Kentang Berpenggerak Motor Listrik - Marni Oktavia; Adi Nugroho (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Universal, 2024)
This research examines the effectiveness of the manual potato washing process and explores the use of an electric motor-based washing machine as an alternative solution. The machine was designed to improve washing efficiency and ensure the potatoes reach a predetermined standard of cleanliness. The focus of the research was to determine the duration required for the machine to wash the potatoes clean. The methodology used included direct observation and literature study. Data analysis was done quantitatively, with the application of Measurement System Analysis (MSA) to assess the consistency of the measuring instruments used. A 5 kg sample of potatoes was washed in three test iterations. Washing quality was measured using a nominal scale that included three key characteristics of clean potatoes. Results showed that 5 kg of potatoes could be washed to cleanliness standards within 10 minutes. Analysis of variance (ANOVA) yielded a P value of 0.787, indicating no significant difference between test iterations. Meanwhile, Gage R&R indicated a Repeatability value of 0.270833 and Reproducibility of 0.010417, indicating minimal variation between tests conducted by different testers.